2017
DOI: 10.1111/jog.13294
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean myomectomy in modern obstetrics: More light and fewer shadows

Abstract: The study aim was to evaluate management of myomas during cesarean section, the pro and cons and the outcomes of cesarean myomectomy. Moreover, we tried to investigate the long-term outcomes of cesarean myomectomy. The authors conducted a literature review using scientific databases, focusing on the benefits and outcomes of cesarean myomectomy and the recent trends regarding this topic, and identified relevant articles, related references and other papers citing them. Despite the demonstrated advantages of ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 34 publications
(76 reference statements)
1
28
0
20
Order By: Relevance
“…Moreover, the possible risks of re-operation are prevented, while at the same time the cost is also reduced. [19] As a matter of fact, in their study, Liu et al reported that 40% of the myoma cases where myomectomy was not performed during C/S, were re-operated on within 6 to 38 months postoperatively. [20] Some factors to consider for myomectomy during C/S include the number, size and localization of the myomas, the possible effects on uterine contractility, the experience of the surgeon and the facilities at the health institution where the operation is performed.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the possible risks of re-operation are prevented, while at the same time the cost is also reduced. [19] As a matter of fact, in their study, Liu et al reported that 40% of the myoma cases where myomectomy was not performed during C/S, were re-operated on within 6 to 38 months postoperatively. [20] Some factors to consider for myomectomy during C/S include the number, size and localization of the myomas, the possible effects on uterine contractility, the experience of the surgeon and the facilities at the health institution where the operation is performed.…”
Section: Discussionmentioning
confidence: 98%
“…10,12 Adverse obstetric complications are reported in 10%-40% of cases like spontaneous miscarriage, labor dystocia, intrauterine growth restriction, preterm labor, placental abruption, Placenta Previa, fetal malpresentation and postpartum haemorrhage. 4,[8][9][10]12,14…”
Section: Myomas In Pregnancymentioning
confidence: 99%
“…Risk of complications is also increased with submucosal, retro placental, large and multiple fibroids. 4,12 In early pregnancy, chances of spontaneous miscarriage are 8% with single fibroid and 23.6% with multiple fibroids. Early miscarriage and abdominal pain are common when fibroid is located in the body than in lower segment and with intramural or submucosal fibroid.…”
Section: Management Controversy and Complications Of Myomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important advantage of cesarean myomectomy is the improved quality of life in affected women. However, they concluded that the risk benefit of cesarean myomectomy should be re-evaluated and further research is necessary [28]. Song et al reviewed myomectomy during cesarean section through the database search and among 2500 studies they found nine studies eligible for their review and concluded that cesarean myomectomy may be a reasonable option in some leiomyoma patients but data driven from the meta-analysis were low quality, and definitive conclusion on this issue cannot be drawn [29].…”
Section: Contraindications Of Cesarean Myomectomy Are Listed Inmentioning
confidence: 99%